KONFLIK BATIN TOKOH UTAMA NOVEL TEMBANG ILALANG KARYA MD. AMINUDDIN TAHUN PELAJARAN 2012/2013 - Wahlin, Wahlin; Nasution, Ismail; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
The research was distributed by inner conflict and about the labyrinth of the life of a character named Asroel who was often confronted with environments that are less supportive of his efforts. Formulation of the problem of the research is